Long term low emission and climate resilient development strategies - Chesterman, Sabrina; Chevallier, Romy (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Two sets of slides used to deliver the module on long-term climate resilient development strategies within the AGNES-led Climate Governance, Diplomacy and Negotiations Leadership Program